The Model of „Hidden Factory” Costs’ Sources: The Executives’ Perspective. Part 2: The Analytical Matrixes - Woźniak, Jacek (Management and Administration Journal, 2023)
Managing the level and scale of hidden costs is a complex and multifaceted activity. That is why it is necessary, especially at executive level, to make the specification for the basic criteria (dimensions) of the identification and analysis of the sources of this cost category. One of the tools possible to use are the analytical matrixes, which are a result of the compilation of the chosen criteria. The matrixes are a specific link between the strategic and operational management, as well as between the theoretical assumptions of the model of identification and analysis of the sources of HFC ("hidden factory" costs) phenomenon from the perspective of executives, and the management practice (e.g. in an aspect of the complexity of the decision-making process). The basic analytical criteriainclude: the complexity of the decision-making processes, the degree of the awareness of the degree of error, the impact on the state of the processes carried out at workstation level, the area of the hidden costs’ appearance, the degree of the knowledge management processes’ advancement, and the level of the process maturity in an organization.